KIT DIAGNOSTIK DIFTERI BERBASIS HIBRIDISASI DNA - billgerd Tjengal; Almira Alifia; Novia Syari Intan (Berkala Ilmiah Mahasiswa Farmasi Indonesia, 2019)
Introduction: Diphtheria is an upper respiratory tract infection caused by Corynebacterium diphtheria bacterium. The recent diphtheria outbreak caused a large number of deaths in rapid period. This is due to the absence of a fast and precise method of diphtheria diagnosis. Current diagnosis practices aredone by cultivating bacteria which takes a relatively long time, which is 3 to 5 days, while the patients may already develop severe infection by the time the results are accessible. Therefore, a sensitive, easy and fast diphtheria diagnostic method is needed so that patients suspected of being infected can betreated quicker.Methods: This advertorial is written based on literature study method.Result: The diphtheria diagnostic kit was designed based on the DNA hybridization method by using DNA microarray. There are probes on the microarray plate in the form of a single stranded DNA fragment that is complement to the unique area of gene that encodes diphtheria toxin. The test sample wasobtained from the preparation of the patient's throat smear and labeled with a fluorescence marker before dropped onto the plate. Thus, if there is diphtheria DNA in the patient's sample, hybridization will occur between diphtheria DNA and the complementary DNA probe. The occurrence of hybridization will be characterized by fluorescence as an indicator of whether patients have diphtheria or not. The application of this diagnostic kit can shorten the diagnosis of C. diphtheria to less than 24 hours .Conclusion: Diphtheria diagnostic kit based on DNA hybridization can be made and applied.